Reconstructing post-conflict cultures: a case study of Bosnia - Pupavac, Vanessa (Zoilus Press, 2006)
Over the last decade tremendous interest has been expressed by international organisations such as UNESCO in the “deep cultural roots” of war. Cultural reform programmes are regarded today as a crucial component of international peace efforts. This chapter considers how international reconstruction efforts now encompasses cultural reform through a case study of peace building efforts in Bosnia. I begin by considering the understanding of culture held by international organisations before going on to examine international culture of peace models and their implementation in Bosnia. My research critically analyses the implications of international programmes for cultural autonomy and social cohesion in Bosnia.